2019
DOI: 10.1080/17290376.2019.1626760
|View full text |Cite
|
Sign up to set email alerts
|

Youth living with HIV/AIDS in secondary schools: perspectives of peer educators and patron teachers in Western Uganda on stressors and supports

Abstract: As Youth Living With HIV/AIDS (YLWHA) continue to survive and live with HIV chronically due to effective Antiretroviral Therapy (ART), it is paramount to work toward maximising their psychosocial wellbeing. The school where these YLWHA are expected to spend most of their time is an excellent environment to investigate this. In this study, we explore perspectives of Peer Educators (PEs) in secondary schools of one district in Western Uganda on how YLWHA are perceived in school, on their daily stressors and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
(71 reference statements)
8
27
0
Order By: Relevance
“…Considering the community readiness model [34], we hold that school communities by default need to be ready to receive and support YLWHA rather than instituting supportive measures following in-school disclosures. Since HIV is prevalent in this locality [14] and it is a highly stigmatized condition [16], schools should be at a high level of readiness regardless of any disclosures. Regrettably, our ndings seem to place these schools at the level of vague awareness [35] in which the community is concerned about the health issue -in this case inclusion and support for YLWHA -but the motivation to address it is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the community readiness model [34], we hold that school communities by default need to be ready to receive and support YLWHA rather than instituting supportive measures following in-school disclosures. Since HIV is prevalent in this locality [14] and it is a highly stigmatized condition [16], schools should be at a high level of readiness regardless of any disclosures. Regrettably, our ndings seem to place these schools at the level of vague awareness [35] in which the community is concerned about the health issue -in this case inclusion and support for YLWHA -but the motivation to address it is low.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Ugandan secondary schools has shown that YLWHA are particularly vulnerable to HIVrelated stigma, abuse, poor nutrition, mental and physical health di culties, and poverty [12,[14][15][16][17]. In addition, they often come from households that are economically challenged due to a high burden of healthcare-related costs and loss of income due to ill or deceased adult members [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these youth have been facilitated to live longer with HIV as a chronic infection due to Antiretroviral Therapy (ART) [4], yet concerns about their Quality of Life (QoL) have risen. HIV-related stigma has been found to be a key stressor affecting QoL of these youth [1,5]. Although several studies have elaborated how HIV-related stigma undermines the HIV management cascade for youth [6][7][8][9][10], little attention has been devoted to the lived experiences of YLWHA with HIV-related stigma and its effects on their daily life especially in the Ugandan context.…”
Section: Introductionmentioning
confidence: 99%
“…The possible systematic variation across HIV groups in the relationship of adversity and social support to psychosocial adjustment has not been specifically investigated. This understanding is important for targeting the most vulnerable children for interventions to improve psychosocial adjustment in sub‐Saharan Africa countries where HIV prevalence is high but resources are limited, and cumulative lifetime adversity may vary according to perinatal HIV status (Kimera et al., 2019; Menon, Glazebrook, Campain, & Ngoma, 2007; Sanjeeva, Pavithra, Chaitanya, Sunil Kumar, & Rewari, 2016). In order to address this gap, we present longitudinal data on cumulative lifetime adversity, social support, and psychosocial adjustment from a large cohort that includes perinatally HIV infected (PHIV), HIV exposed uninfected (HUU) and HIV unexposed uninfected children.…”
Section: Introductionmentioning
confidence: 99%